2000
DOI: 10.1007/s004059900208
|View full text |Cite
|
Sign up to set email alerts
|

Serum levels of vascular endothelial growth factor in patients with head and neck cancer

Abstract: Angiogenesis is now considered to be crucial for tumor growth and metastasis. In several tumors, microvascular density has been shown to be correlated with metastasis and aggressiveness. Vascular endothelial growth factor (VEGF) is a secreted endothelial cell-specific mitogen, which is induced by hypoxia and is angiogenic in vivo. VEGF has been identified in a wide variety of malignancies including head and neck squamous cell carcinomas (HNSCC). We investigated the circulating level of VEGF in sera from patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
24
0
5

Year Published

2001
2001
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(32 citation statements)
references
References 29 publications
(45 reference statements)
3
24
0
5
Order By: Relevance
“…In our study, serum VEGF-A level was found to be significantly higher (p=0.001) in SCCHN patients as compared to healthy controls. A similar study previously done by Riedel et al (2000), De Schutter et al (2005) and Hong et al (2009) found that serum VEGF-A level is elevated in head and neck cancer patients as compared to healthy controls.…”
Section: Discussionsupporting
confidence: 79%
“…In our study, serum VEGF-A level was found to be significantly higher (p=0.001) in SCCHN patients as compared to healthy controls. A similar study previously done by Riedel et al (2000), De Schutter et al (2005) and Hong et al (2009) found that serum VEGF-A level is elevated in head and neck cancer patients as compared to healthy controls.…”
Section: Discussionsupporting
confidence: 79%
“…Others have also described the development of peliosis in the setting of known malignancies, including renal cell carcinoma, pancreatic cancer, and Wilm's tumor (28)(29)(30). With respect to VEGF as a mediator of this particular paraneoplastic syndrome, it has been well established that many human cancers secrete VEGF, and that in some instances, elevated levels of VEGF can be detected in sera of patients with advanced malignancy (31)(32)(33)(34). Moreover, there seems to be a correlation between serum VEGF levels and prognosis (33,(35)(36)(37).…”
Section: Resultsmentioning
confidence: 99%
“…One strategy in novel approaches to cancer therapy is the inhibition of angiogenesis of malignant tumors. Various studies detect the induced angiogenic response in vivo, and the correlation between high microvessel counts and recurrent or metastatic disease in HNSCC (51,52). A variety of angiogenic factors released from tumor cells and the extracellular matrix regulate the induction of tumor vascularization.…”
Section: Discussionmentioning
confidence: 99%
“…Enhanced expression of VEGF has been detected in a number of malignant human tumors, including HNSCC (49,50). VEGF expression in HNSCC tumors is strongly correlated with tumor angio genesis and is inversely correlated with apoptosis (51,52), which illustrates the anti-apoptotic potential of VEGF. For example, VEGF expression could be induced by loss or inactivation of tumor suppressor genes or overexpression of oncogenes.…”
Section: Chemotherapeutic Alteration Of Vegf-/pdgf-and Pdgf-rα/β Exprmentioning
confidence: 99%
See 1 more Smart Citation